ANALISIS PENDAPATAN USAHA SARANG BURUNG WALET DI DESA WOWOLI KECAMATAN TOARI KABUPATEN KOLAKA - Ananta, Astin; Triani, Neks; Syahrir, Sasmita Nabila (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the income generated from swallow's nest business in Wowoli Village, Toari Sub-district, Kolaka District. The main focus of this study was on three local entrepreneurs, namely Mr. Irham, Mr. Marsaid, and Mr. Yusuf, who each have different approaches and strategies in running their businesses. The data sources used include primary data obtained through direct interviews and field observations, as well as secondary data from related documents and reports. The approach adopted was qualitative, allowing the researcher to gain an in-depth understanding of the dynamics of the swallow's nest business in the area. The results showed that the income from the swallow nest business run by Mr. Irham, which was established in 2014, as well as the businesses of Mr. Marsaid and Mr. Yusuf, which were each established in 2019, experienced consistent growth each year. Mr. Irham's business income reached Rp 432,825,000, far exceeding Mr. Marsaid's income of Rp 96,465,000 and Mr. Yusuf's of Rp 94,685,000. From this analysis, it can be concluded that the swallow nest business in Wowoli Village has significant profit potential, especially if managed efficiently. In addition to the size of the building and the number of floors, other factors that affect the income include the length of the business, strategic location, temperature and humidity of the building, and the quality of the nests produced. Keywords: Income, Business, Swallow's Nest, UMKM